2017
DOI: 10.1093/bioinformatics/btx367
|View full text |Cite
|
Sign up to set email alerts
|

MoDMaps3D: an interactive webtool for the quantification and 3D visualization of interrelationships in a dataset of DNA sequences

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…A pairwise distance matrix is then computed using the Pearson Correlation Coefficient (PCC) [54] as a distance measure between magnitude spectra. The distance matrix is used to generate the 3D Molecular Distance Maps (MoDMap3D) [55] by applying the classical Multi-Dimensional Scaling (MDS) [56]. MoDMap3D represents an estimation of the relationship among sequences based on the genomic distances between the sequences.…”
Section: Methodsmentioning
confidence: 99%
“…A pairwise distance matrix is then computed using the Pearson Correlation Coefficient (PCC) [54] as a distance measure between magnitude spectra. The distance matrix is used to generate the 3D Molecular Distance Maps (MoDMap3D) [55] by applying the classical Multi-Dimensional Scaling (MDS) [56]. MoDMap3D represents an estimation of the relationship among sequences based on the genomic distances between the sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Six supervised machine learning classifiers (Linear Discriminant, Linear SVM, Quadratic SVM, Fine KNN, Subspace Discriminant, and Subspace KNN) are trained on this pairwise distance vectors, and then used to classify new sequences. Independently, classical multidimensional scaling generates a 3D visualization, called Molecular Distance Map (MoDMap) [43], of the interrelationships among all sequences.…”
Section: Supervised Machine Learningmentioning
confidence: 99%
“…These points can then be simultaneously visualized in a 2-or 3-dimensional space by taking the first 2, respectively 3, coordinates (out of q) of the coordinate matrix. The result is a Molecular Distance Map [43], and the MoDMap of a genomic dataset represents a visualization of the simultaneous interrelationships among all DNA sequences in the dataset.…”
Section: Classical Multidimensional Scaling (Mds)mentioning
confidence: 99%
“…Studies measuring 77 quantitative similarity between DNA sequences from different sources have been 78 performed, for instance using the Manhattan distance [32,33], the weighted or 79 standardized Euclidean distance [34,35], and the Jensen-Shannon distance [36,37]. 80 Applications of these distances and others have been compared and benchmarked 81 in [38][39][40][41], and detailed reviews of the literature can be found in [42][43][44][45]. 82 In the context of viral phylogenetics, k-mer frequency vectors paired with a distance 83 metric have been used to construct pairwise distance matrices and derive phylogenetic 84 trees, e.g., dsDNA eukaryotic viruses [46], or fragments from Flaviviridae genomes [47].…”
mentioning
confidence: 99%
“…Next, the distance matrix is visualized by classical MultiDimensional Scaling (MDS) [80]. 176 MDS takes as input a pairwise distance matrix and produces as output a 2D or 3D plot, 177 called a MoDMap [81], wherein each point represents a different sequence, and the 178 distances between points approximate the distances from the input distance matrix. As 179 MoDMaps are constrained to two or three dimensions, it is in general not possible for 180 the distances in the 2D or 3D plot to match exactly the distances in the distance 181 matrix, but MDS attempts to make the difference as small as possible.…”
mentioning
confidence: 99%